Close observation unit lancashire women and newborn centre – the first year. (18th April 2012) - Dewolage, M; Clarke, FR; Shaw, G
Abstract : Lancashire Womens and Newborn Centre was created in November 2012 following the merger of the Blackburn and Burnley Maternity Units. The Close Observation Unit on the Birth Suite is a two bedded area staffed by a group of specially trained midwives supported by the Consultants. Audit Standards: CNST slandered and local Trust guidelines (severely ill women and high dependency care). Method: Prospective audit of 70 cases admitted to close observation unit (March to September 2011). Results: There were 114 admissions over the 7 month period (16.28/Month). Majority of patients represented 20 to 30 years age group and 97.1% represented postnatal mothers. Reason for admission were APH/PPH (47.1%), PET (22.8%), sepsis (12.3%), unstable observations (7.14%), diabetes (2.9%), heart disease (2.9%), epilepsy (1.4), respiratory problems (1.4%) respectively. Consultant involvement in the management of these patients was seen in 91.4% by the consultant obstetrician and 71.4% by the consultant anaesthetist. Thirteen patients were referred to other specialities and consultant anaesthetist and obstetrician were involved in the decision making in all these patients. Attendance at the ALERT course and ILS were completed by 75% and 50% of midwives managing the unit respectively. The Unit demonstrated 100% compliance with availability of pumped O2.continuous ECG monitoring, non invasive BP monitoring and O2 saturation monitoring. Conclusion: admissions figures in line with national estimates. Unit complied with most of audited criteria. Areas for development include staff training and consultant involvement in patient management.